2015
DOI: 10.2105/ajph.2015.302752
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Food Security for US Farmworker Households and Factors Related to Dynamic of Change

Abstract: Objective We examined food security indicators in 248 farmworker families with pre-school age children over 24 months to identify food security patterns and examine the dynamic of change over time. Methods Participants in the Niños Sanos study, conducted 2011 to 2014, completed quarterly food security assessments. Based on responses to items in the US Household Food Security Survey Module, we identified different states of food security using hidden Markov model analysis, and examined factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…And the most recent Brazilian survey with perception scale revealed that the number of Brazilian households with some degree of FI per EBIA classification was 22.6%, is lower than the value found herein (49.5%) (IBGE, 2014). The prevalence of food insecurity in studies conducted in India and the United States with rural households using perceptual scores was similar to that of this study, with 40% of Indian households and 51% of households in the state of North Carolina (BAUER et al, 2012;IP et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…And the most recent Brazilian survey with perception scale revealed that the number of Brazilian households with some degree of FI per EBIA classification was 22.6%, is lower than the value found herein (49.5%) (IBGE, 2014). The prevalence of food insecurity in studies conducted in India and the United States with rural households using perceptual scores was similar to that of this study, with 40% of Indian households and 51% of households in the state of North Carolina (BAUER et al, 2012;IP et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…24 “Sites” are organizations or locations with which members of the target community are associated, such as Head Start programs and community health centers. Community data collectors also conducted door-to-door recruitment in Latino neighborhoods and farmworker camps, and contacted previous study participants.…”
Section: Methodsmentioning
confidence: 99%
“…Niños Sanos is a longitudinal two-year study designed to describe the dietary and physical activity patterns of young children of Latino farmworkers in North Carolina. 6,10 Eligible participants were self-identified Latino women with a co-resident child aged 2.5 to 3.5 years and at least one member of the household engaging in farm work during the previous year. The study focused on 2.5 to 3.5 year old children because this is an age when eating and feeding practices are established.…”
Section: Methodsmentioning
confidence: 99%
“…69 These children often reside in low-income, rural, immigrant households, a context that may limit access to nutritious food and hinder safe and appropriate forms of physical activity. 10 Given that many farmworkers are undocumented and migrate, some parents may be unable to utilize government safety net programs intended to ensure children’s access to healthy foods and health care. 3,11,12 Parents may receive little guidance regarding children’s diet and fail to recognize children with excess weight as being at risk for health issues.…”
Section: Introductionmentioning
confidence: 99%